Интуиция как форма познания - Худаева, С. А.; Яковлев, А. А. (ХНУРЕ, 2019)
People explore the world and their own nature and one of the most interesting ways of knowing is intuition. This special skill makes it possible to decide. It is not based on logical conclusions, but on the sixth sense. Intuition is creative process, the power of insight. It is complete opposite of ordinary logical thinking. Intuition at the household level is characterized as intuition, subtle understanding, and insight into the essence. It is opportunity to look at things from a different angle.
Keywords: проблематика философская; мир чувственный; интуиция; чутье; проницательность; понимание тонкое